2018
DOI: 10.5607/en.2018.27.4.267
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Attenuates Neuropathic Pain by Inhibiting P2X7R Expression and ERK Phosphorylation in Rats

Abstract: α2-Adrenoceptor agonists attenuate hypersensitivity under neuropathic conditions. However, the mechanisms underlying this attenuation remain largely unknown. In the present study, we explored the potential roles of purinergic receptor 7 (P2X7R)/extracellular signal-regulated kinase (ERK) signaling in the anti-nociceptive effect of dexmedetomidine in a rat model of neuropathic pain induced by chronic constriction injury (CCI) of the sciatic nerve. An animal model of CCI was adopted to mimic the clinical neuropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 54 publications
2
36
0
Order By: Relevance
“…In this study, we investigated the putative link between CXCL10/CXCR3 signaling-mediated BSCB disruption and neuropathic pain. As in our previous studies, CCI group rats exhibited robust post-operative behavioral hypersensitivity to mechanical stimuli, and this hypersensitivity persisted throughout the experimental period (29,32). We also determined that CCI induced CXCL10/CXCR3 signaling, increased BSCB permeability, and promoted T cell migration into the spinal dorsal horn.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In this study, we investigated the putative link between CXCL10/CXCR3 signaling-mediated BSCB disruption and neuropathic pain. As in our previous studies, CCI group rats exhibited robust post-operative behavioral hypersensitivity to mechanical stimuli, and this hypersensitivity persisted throughout the experimental period (29,32). We also determined that CCI induced CXCL10/CXCR3 signaling, increased BSCB permeability, and promoted T cell migration into the spinal dorsal horn.…”
Section: Discussionsupporting
confidence: 68%
“…Hyperalgesia was assessed based on paw withdrawal responses to a calibrated series of von Frey filaments (Stoelting; Wood Dale, IL, USA) as described in one of our earlier publications (32). In brief, the rats were individually placed in a chamber (20 cm × 10 cm × 20 cm) in which the floor was a customized platform consisting of a grid of iron wires with 10-mm spacings between wires.…”
Section: Von Frey Test For Hypersensitivity To Mechanical Stimulationmentioning
confidence: 99%
“…Analgesic drugs, such as dexmetomidine, type-2 cannabinoid receptor agonists, and ketamine alleviate neuropathic pain by restraining MAPK activation in the spinal cord. [70][71][72] In dorsal horn neurons, MAPK phosphorylates and inhibits K v 4.2 channels, which mediate type-A potassium currents and are involved in pain plasticity. [73][74][75] It is possible that NAC treatment in diabetic mice enhances the activity of K v 4.2 channels, therefore reducing excitability of secondary order neurons in the dorsal horns of the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine, a selective α2 adrenergic receptor (AR) agonist, provided analgesic potency via systemic administration, also, low does of dexmedetomidine relieved tactile allodynia induced by neuropathic pain model (5). Moreover, study demonstrated that dexmedetomidine might a better adjuvant for clinical procedure and pain management for neuropathic pain in clinic (6,7).…”
Section: Introductionmentioning
confidence: 99%